Bună,
6.
[tex]c) \sqrt{12} \times ( \sqrt{32} - 3 \sqrt{3} ) - 4(7 + 2 \sqrt{6} ) = \\ 2 \sqrt{3} \times (4 \sqrt{2} - 3 \sqrt{3} ) - 28 - 8 \sqrt{6} = \\ 8 \sqrt{6} - 18 - 28 - 8 \sqrt{6} = \\ - 18 - 28 = \\ - 46[/tex]
[tex]d) \sqrt{48} \times ( \sqrt{8} - \sqrt{3} ) - 2 \sqrt{2} \times (4 \sqrt{3} - \sqrt{2} ) \\ 4 \sqrt{3} (2 \sqrt{2} - 3 ) - 8 \sqrt{6} + 4 = \\ 8 \sqrt{6} - 12 - 8 \sqrt{6} + 4 = \\ - 12 + 4 = - 8[/tex]
7.
[tex]a)4 \times ( \sqrt{5} - 2 \sqrt{2} ) + 3(7 \sqrt{5} - 4 \sqrt{2} ) - 7( \sqrt{2} - 3 \sqrt{5} ) = \\ 4 \sqrt{5} - 8 \sqrt{2} + 21 \sqrt{5} - 12 \sqrt{2} - 7 \sqrt{2} + 21 \sqrt{5} = \\ 46 \sqrt{5} - 27 \sqrt{2} [/tex]
[tex]b) \sqrt{63} - 3(2 \sqrt{7} - 4 \sqrt{3} ) + 4(2 \sqrt{3} + 5 \sqrt{7} ) = \\ 3 \sqrt{7} - 6 \sqrt{7} + 12 \sqrt{3} + 8 \sqrt{3} + 20 \sqrt{7} = \\ 17 \sqrt{7} + 20 \sqrt{3} [/tex]
Sper că te-am ajutat